Bypassing primary care clinics for childbirth: a cross-sectional study in the Pwani region, United Republic of Tanzania - Margaret E Kruk; Sabrina Hermosilla; Elysia Larson; Godfrey M Mbaruku
Objective To measure the extent, determinants and results of bypassing local primary care clinics for childbirth among women in rural parts of the United Republic of Tanzania. Methods Women were selected in 2012 to complete a structured interview from a full census of all 30 076 households in clinic catchment areas in Pwani region. Eligibility was limited to those who had delivered between 6 weeks and 1 year before the interview, were at least 15 years old and lived within the catchment areas. Demographic and delivery care information and opinions on the quality of obstetric care were collected through interviews. Clinic characteristics were collected from staff via questionnaires. Determinants of bypassing (i.e. delivery of the youngest child at a health centre or hospital without provider referral) were analysed using multivariate logistic regression. Bypasser and non-bypasser birth experiences were compared in bivariate analyses. Findings Of 3019 eligible women interviewed (93% response rate), 71.0% (2144) delivered in a health facility; 41.8% (794) were bypassers. Bypassing likelihood increased with primiparity (odds ratio, OR: 2.5; 95% confidence interval, CI: 1.9-3.3) and perceived poor quality at clinics (OR: 1.3; 95% CI: 1.0-1.7) and decreased if clinics recently underwent renovations (OR: 0.39; 95% CI: 0.18-0.84) and/or performed ≥ 4 obstetric signal functions (OR: 0.19; 95% CI: 0.08-0.41). Bypassers reported better quality of care on six of seven quality of care measures. Conclusion Many pregnant women, especially first-time mothers, choose to bypass local primary care clinics for childbirth. Perceived poor quality of care at clinics was an important reason for bypassing. Primary care is failing to meet the obstetric needs of many women in this rural, low-income setting.